2021
DOI: 10.1016/j.ekir.2021.08.020
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Evocalcet in Previously Cinacalcet-Treated Secondary Hyperparathyroidism Patients

Abstract: Introduction: Evocalcet is a recently approved calcimimetic agent for secondary hyperparathyroidism (SHPT). In this study, the efficacy and safety of once-daily oral evocalcet were evaluated in patients without prior cinacalcet use (nonusers) and previously treated patients (users).Methods: This post hoc analysis of a previous phase III head-to-head comparison study included SHPT patients treated with evocalcet with or without prior cinacalcet use. Endpoints included trends in the median intact and whole parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For SS patients, there is no effective treatment currently, but medication or surgery can be utilized as a feasible means for proper control of PTH. In a prospective study, calcimimetics Cinacalcet and Etelcalcetide demonstrated high e cacy in the treatment of SHPT, accompanied by improved clinical outcomes such as the incidence of bone fractures, cardiovascular morbidity and mortality in hemodialysis patients [24,25]. For presently, subtotal parathyroidectomy, total parathyroidectomy, and total parathyroidectomy plus auto-transplantation constitute the main surgical methods for secondary hyperparathyroidism [26].…”
Section: Discussionmentioning
confidence: 99%
“…For SS patients, there is no effective treatment currently, but medication or surgery can be utilized as a feasible means for proper control of PTH. In a prospective study, calcimimetics Cinacalcet and Etelcalcetide demonstrated high e cacy in the treatment of SHPT, accompanied by improved clinical outcomes such as the incidence of bone fractures, cardiovascular morbidity and mortality in hemodialysis patients [24,25]. For presently, subtotal parathyroidectomy, total parathyroidectomy, and total parathyroidectomy plus auto-transplantation constitute the main surgical methods for secondary hyperparathyroidism [26].…”
Section: Discussionmentioning
confidence: 99%
“…CaSR activation and the subsequent STC2 increase have putative anti-apoptotic effects against high phosphate. These findings make a meaningful contribution to the clinical treatment of VSMC injury because calcimimetics have been used in secondary hyperparathyroidism treatment of CKD patients for several years [29]. Although the EVOLVE trial did not obtain positive results [16], an imbalance in the subject age at randomization and discontinuation rates are reasons for the lack of demonstrating a benefit to mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the study suggest that evocalcet treatment is effective and safe, regardless of prior cinacalcet treatment. Given the concerns about long-term exposure to high blood-PTH concentrations, these results suggest that patients may benefit if they start evocalcet treatment in the early stages of SHPT [45]. In turn, in a direct comparative study of dialysis patients in Japan using evocalcet and cinacalcet, it was found that evocalcet was as effective in lowering serum PTH levels as cinacalcet, but it caused fewer side effects and fewer drug interactions [46].…”
Section: Calcimimeticsmentioning
confidence: 95%
“…Calcium and phosphate imbalances associated with CKD are defined by the Kidney Disease Improvement Global Outcomes (KDIGO) group as chronic kidney disease-metabolic bone disease (CKD-MBD). CKD-MBD includes bone complications that can lead to chronic pain syndromes and mobility limitations, cardiovascular complications, significantly increasing mortality in this group of patients, and soft tissue calcifications [1,2,3]. The last guidelines for the treatment of SHPT in the course of CKD were published by KDIGO in 2017 and have not been updated.…”
mentioning
confidence: 99%